An Innovative Spool-Type Pressure Feedback Restrictor for Hydrostatic Bearings. Issue 4 (1st October 2016) - Renn, Jyh-Chyang; Hsu, Wen-Jen; Li, Yun-Ruei
Abstract: This study presents the design of a novel single-acting spool-type pressure feedback restrictor for hydrostatic bearings. The increasing demand for larger machine tools that will handle heavy loads with precision has resulted in much attention being directed toward the development of hydrostatic bearings. At present, the most commonly used pressure feedback restrictor for hydrostatic bearings employs a membrane. In the membrane device, a flexible metal diaphragm is the key component and this kind of restrictor can provide precise metering of hydraulic oil flow. However, the membrane device is not suitable for extremely heavy loads and we present a spool type of pressure feedback restrictor as an alternative. This type of restrictor can support much heavier loads than the membrane type and is suitable for the bearings in large machine tools. The novel design has two significant features: the first is the orifice restrictor which effectively circumvents the influence of fluctuating oil temperature. The second feature is the introduction of adjustment screws at each end of the valve body which widen the range of operation. A prototype was successfully fabricated and the experimental results validate the design of this new and innovative pressure feedback restrictor. Abstract :